Pengaruh Variabel Makroekonomi terhadap Investasi Asing Langsung di Indonesia - Fradya Randa (SAFE-Network, 2023)
This study aims to analyze the short-term and long-term relationships between macroeconomic variables and the flow of Foreign Direct Investment (FDI) in Indonesia from 1982 to 2021. The analysis model used is johansen-juselius co-integration and error correction model (ECM. This study found a cointegration relationship between macroeconomic variables and FDI inflows. Money supply is a factor that influences FDI inflows in the short and long term. Meanwhile, inflation and trade openness have a negative effect in the long term. Market size affects FDI inflows only in the short term. This finding has implications that the government needs to maintain the stability of macroeconomic variables to increase FDI inflows.